Current scenario of insect pests and mite on drumstick (Moringa oleifera) in south India and their management - PRASANNAKUMAR, N R; BHAT, P SHIVARAMA; JYOTHI, N; SAROJA, S (The Indian Journal of Agricultural Sciences, 2024)
Dynamics of insect pests play a crucial role in understanding their occurrence on a crop. Many insect pests infest on drumstick at various phenophase of the crop and limit the productivity. In the present study, the current scenario of insect pest as well as beneficial arthropods associated with drumstick was assessed and developed appropriate management strategies for major pests. The arthropods found on drumstick was leaf eating caterpillar (Noorda blitealis), aphids (Aphis craccivora), tea mosquito bug (Helopeltis antonii), bihary hairy caterpillar (Spilosoma obliqua), stem borer (Batocera rubus Batocera) and pod fly (Gitona distigma).The beneficial insects include coccinellid beetles, Cocinella septmpunctata Linnaeus, spiders: Oxyopes shweta Tikader (Oxyopidae), Thomisus spp (Thomisidae), Nescona sp and braconid wasp, Disophrys sp.; pollinators such aslittle bee-Apis florea Fab. and bumble bee, Bombus spÂ were recorded on drumstick. The information generated in the study would help in initiating the appropriate pest management strategies at right time to minimize Â pesticide residue on the crop.Â